Does the use of incretin‐based medications increase the risk of cancer in patients with type‐2 diabetes mellitus?. Issue 4 (18th February 2019) - Karp, Igor; Sivaswamy, Atul; Booth, Christopher
Abstract: Purpose: Incretin‐based medications are a novel class of agents for the treatment of type‐2 diabetes mellitus (DM2). The safety profile of these medications is not firmly established, and concerns have been raised about their potential carcinogenicity. The objective of our study was to produce new evidence on the effect of incretin‐based medications on cancer risk in patients with DM2. Methods: We conducted a "retrospective cohort" study with data from the Clinical Practice Research Datalink and the Hospital Episodes Statistics in the UK. New users of either an incretin‐based medication ( n  = 18 885) or a sulfonylurea medication ( n  = 36 929) between 2007 and 2013 were identified and followed for up to 8 years. Cox proportional‐hazards models were used to estimate the quasi‐intention‐to‐treat and quasi‐per‐protocol hazard‐ratios for the association between incretin‐based medications with cancer while adjusting for potential confounders. Results: The adjusted hazard ratio (95% confidence interval) for use of incretin‐based medications versus use of sulfonylurea medications for the overall‐cancer outcome was 0.97 (0.90, 1.05) in the quasi‐intention‐to‐treat analysis and 0.90 (0.81, 1.00) in the quasi‐per‐protocol analysis. In both analyses, the hazard‐ratio functions over the 8‐year follow‐up seemed fairly constant, and the 8‐year cumulative‐risk functions in the two subcohorts were similar. Conclusions: Our study suggests that the use of incretin‐based medications in patients with DM2 does not increase the risk of cancer relative to the use of sulfonylurea medications, at least in the first several years of the use. Further research is needed to assess long‐term effects of the use of incretin‐based medications on cancer risk.